2010
DOI: 10.1177/0363546510382852
|View full text |Cite
|
Sign up to set email alerts
|

Foot Orthoses in the Prevention of Injury in Initial Military Training

Abstract: In this military trainee population, orthoses were effective in the prevention of overuse lower limb injury. This is the first study to identify a positive preventive role of orthoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 44 publications
2
68
0
1
Order By: Relevance
“…Lower limb MSKI have been most frequently reported [1,[5][6][7][8][9][10]. Heir, et al [8] Found 63% of injuries were sited on the lower limb, similarly Robinson, et al [5] found 81% of MSKI reported by British Infantry recruits to be located in the lower limb whilst Almeida, et al [9] reported a slightly higher rate, 82%, in American recruits.…”
Section: Injury Typementioning
confidence: 99%
See 2 more Smart Citations
“…Lower limb MSKI have been most frequently reported [1,[5][6][7][8][9][10]. Heir, et al [8] Found 63% of injuries were sited on the lower limb, similarly Robinson, et al [5] found 81% of MSKI reported by British Infantry recruits to be located in the lower limb whilst Almeida, et al [9] reported a slightly higher rate, 82%, in American recruits.…”
Section: Injury Typementioning
confidence: 99%
“…The British military is not excluded from this observation [1,5]. These injuries are identified as having negative impact on injury rates, training time, resources and manning [1,3,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidence is reported to range widely from 20% [5], 42% [6] 47% [7], 48% [8,9], 58% [10], 59.7% [11] 75% [12] to as much as 86% in parachute regiment [2,8]. The primary cause of hospitalisations and out-patient visits, MSKI are considered accountable for up to 25 million limited working days annually [13].…”
Section: Introductionmentioning
confidence: 99%
“…MSKI have long been recognised to represent a signifi cant challenge to the effi ciency and therefore operational effectiveness of global military populations [1,[9][10][11][12][13][14][15][16][17][18][19][20][21]. The incidence of MSKI within infantry training establishments has drawn specifi c attention with injury rates reported to range globally from 20% to 60% [1][2][3][4]6,8,15,16].…”
Section: Introductionmentioning
confidence: 99%